Liver transplantation in Wilson’s disease: Long-term experience of single center (Annals of Medical Research, 2021)
Aim: Liver transplantation (LT) is the most effective treatment method for preventing progressive and lethal complications of Wilson’s disease (WD). Despite the deceased donor liver transplantation (DDLT) and living donor liver transplantation (LDLT) are performed in many centers for WD, a limited number of reports were published, about long-term results. The aim of this study is to share the long-term outcomes of single center.Material and Methods: Patients who underwent LT for the WD, between 1997 and 2017 were included. Patient’s survival data, death causes, neurological symptoms and follow-up data were analyzed retrospectively.Results: Eighteen patients (8DDLT, 10LDLT) with the median age of 17.11±9.88 (6-43) were included. Donor relationship was familial in all LDLT patients. Median follow-up time was 80.57±67.59 (0.23-240.9) months and the median survival time was 173.74±25.13 months. Two patients (11.1%) died in the perioperative period (0-90 days) and totally 3 patients (16.6%) died in the postoperative 0-12 month’s period. The survival rates of the patient’s at 1-, 5- and 10 years were 83.3%, 75% and 67.3%, respectively. After LT, neurological symptoms disappeared in 6 of 7 patients and no improvement was observed in one patient. During follow-up period, chronic rejection was seen in 5 patients, 3 patients were treated with medical procedure and 2 patients died due to chronic rejection.Conclusions: Our findings are consistent with the literature, long-term survival is achieved in patients with no mortality, in the postoperative 0-12 month period and after LT, neurological symptoms are disappeared in most of the patients; according to this data, LT is an effective treatment method for the WD and complications.Keywords: Wilson disease; liver transplantation; long term results; living donor.
Keywords: Wilson disease; liver transplantation; long term results; living donor.